LACTIC ACID BACTERIAL SCREENING FROM GASTROINTESTINAL DIGESTIVE TRACT OF NATIVE AND BROILER CHICKEN FOR PROBIOTIC CANDIDATE PURPOSES - Damayanti, E.; Herdian, H.; Angwar, M.; Febrisiantosa, A.; Istiqomah, L. (Diponegoro University, 2012)
The aim of his research was to obtain lactic acid bacteria (LAB) from gastrointestinal digestivetract (GIT) of chickens for probiotic candidate purposes. LAB was isolated from GIT of broiler andnative chickens on selective medium (MRS+0.2% CaCO3). Screening method based on microbiologicaland biochemical characteristics, antibacterial properties, growth on various temperature, aeration, andagitation, antibiotic sensitivity, and viability on acid pH, gastric juice and bile salt. Thirty nine of LABisolates was selected from native chicken and 18 isolates from broiler chicken. The selected LABinhibited Escherichia coli FNCC 0091 growth and grown on 30, 39 and 45oC of temperature, aerobic,anaerobic and agitation conditions. Biochemical identification using API 50 CHL kit revealed that I72from native chicken ileum as Lactobacillus salivarius and Db9 from broiler chicken duodenum asPediococcus pentosaceus. All LAB were resistant to Erythromicin, Penicillin G and Streptomycin astested antibiotics. Both of them have non significantly different of viability on acid pH (1, 2 and 3),gastric juice pH 2 and bile salt which were 91.78% for L. salivarius I72 and 94.48% for P. pentosaceusDb9 (P<0.05). Based on characteristics, both the selected LAB have potentiality as chicken probioticcandidates.